Walker Percy and the Crisis of Meaning Communication in the Ruins - Bonanno, Justin N. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"In this resounding response to contemporary crises of meaning, Justin Bonanno digs deeper than ever before into Walker Percy's philosophical influences, putting us back in touch with existence, showing us how to search for truth across traditions, helping us confront our failure to know ourselves, and revealing the symbolic in-between as the only way to quench our thirst for the real." -Jamin Pelkey, Toronto Metropolitan University, Canada, author Semiotics of X, Co-Editor-in-Chief Semiotica "In this rich and scholarly work, Justin Bonanno demonstrates deep learning by comparatively engaging a wide range of topics and scholars. He powerfully shows how Walker Percy's semiotic theory provides invaluable resources for critiquing nominalism and for leading the way to a robust philosophical realism. For anyone interested in grasping Percy's contributions to philosophy and approach toward a meaningful life, this is must read material." -Corey Anton, Grand Valley State University, USA In this book, Justin N. Bonanno builds off of the recent philosophical work on Walker Percy's writings. While it is valuable to appreciate Percy as a novelist, Bonanno approaches Percy from the perspective of Continental philosophy and the rhetorical tradition. Unpacking the works of several key authors that influenced Percy (e.g. Sartre and Heidegger), Bonanno offers a fresh philosophical account of Percy's ideas concerning the relationship between symbols and existence. In particular, he focuses on how Percy's ideas emerge from the thought of Ernst Cassirer, Susanne Langer, Jacques Maritain, Jean-Paul Sartre, Gabriel Marcel, Martin Heidegger, Viktor Shklovsky, Søren Kierkegaard, and St. Thomas Aquinas. Justin N. Bonanno holds a PhD in rhetoric from Duquesne University, USA. He teaches at Ave Maria University, USA.
Chapter 1: Introduction -- Chapter 2: C1 Consciousness and the Epiphany of Meaning -- Chapter 3: C2 Consciousness and the Unspeakable Self -- Chapter 4: C3 Consciousness and the Defamiliarization of the God-Man -- Chapter 5: Truth and Meaning -- Chapter 6: Love and Meaningfulness.
Keywords: Continental Philosophy; Literature -- Philosophy; America -- Literatures; Continental Philosophy; Philosophy of Literature; North American Literature